ANALISIS DEL CARIOTIPO Y DETECCION DE LOS GENES 5S Y 18S/25S rDNA EN CHAETANTHERA MICROPHYLLA (CASS.) HOOK. ET ARN. (ASTERACEAE) (Gayana Botánica, 2005)
Double fluorescence in situ hybridization was used to examine the karyotype of Chaetanthera microphylla (Cass.) Hook et Arn. from Chile, including the location of 5S and 18S/25S rDNA gene sequences. The species is 2n = 24, with 8m + 4st chromosomes. Signals of 5S and 18/25S rDNA were seen in two of the 12 chromosome pairs: n° 2 and 6.